2004
DOI: 10.1037/0893-3200.18.3.493
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Posttraumatic Stress Symptoms in Adolescent Survivors of Childhood Cancer and Their Families: A Randomized Clinical Trial.

Abstract: Posttraumatic stress symptoms (PTSS), particularly intrusive thoughts, avoidance, and arousal, are among the most common psychological aftereffects of childhood cancer for survivors and their mothers and fathers. We conducted a randomized wait-list control trial of a newly developed 4-session, 1-day intervention aimed at reducing PTSS that integrates cognitive-behavioral and family therapy approaches--the Surviving Cancer Competently Intervention Program (SCCIP). Participants were 150 adolescent survivors and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
234
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 257 publications
(247 citation statements)
references
References 35 publications
5
234
0
4
Order By: Relevance
“…Results from 150 families who participated in SCCIP show significant decline in both arousal and intrusive thoughts in survivors and parents. 62 SCCIP was amended to an intervention aimed at reducing post-traumatic symptoms of a caregiver dyad with a newly diagnosed child with cancer (SCCIP-ND). 63 SCCIP-ND is a three session cognitive-behavioral program for parents of children recently diagnosed with cancer, and it attempts to intervene early in the cancer experience to decrease traumatic stress symptoms by identifying beliefs regarding cancer and cancer treatment and how the cancer experience may affect family functioning.…”
Section: Parents and Familiesmentioning
confidence: 99%
“…Results from 150 families who participated in SCCIP show significant decline in both arousal and intrusive thoughts in survivors and parents. 62 SCCIP was amended to an intervention aimed at reducing post-traumatic symptoms of a caregiver dyad with a newly diagnosed child with cancer (SCCIP-ND). 63 SCCIP-ND is a three session cognitive-behavioral program for parents of children recently diagnosed with cancer, and it attempts to intervene early in the cancer experience to decrease traumatic stress symptoms by identifying beliefs regarding cancer and cancer treatment and how the cancer experience may affect family functioning.…”
Section: Parents and Familiesmentioning
confidence: 99%
“…Concerning children's interventions (patients or cancer survivors), most of them (62.5%) produced mixed results (Barrera et al, 2002, Butler et al, 2008Kazak et al, 2004;McCaffrey 2006;Thygeson et al, 2010). The best results were obtained through the interventions proposed by Barakat et al (2003) and Valencia et al (2006), which could be classified as effective (25.5%).…”
Section: Interventions´ Effectivenessmentioning
confidence: 85%
“…Some studies have found high rates of PSTD symptoms in parents of children with cancer, ranging up to 60% when assessing the overall stress (Kazak et al, 2004, Robinson et al, 2009. In general, according to several studies, it could be stated that parents have more adjustment problems than their children (Phipps et al, 2006), as they present elevated levels of PTSD.…”
Section: Parents´ Psychological Adjustmentmentioning
confidence: 99%
See 2 more Smart Citations